1996
DOI: 10.1007/bf02240940
|View full text |Cite
|
Sign up to set email alerts
|

Dairy cattle crossbreeding in the tropics: Choice of crossbreeding strategy

Abstract: Two strategies for crossbreeding of indigenous and exotic cattle for milk production in the tropics, viz. rotational crossing and formation of a composite breed, have been compared. Genetic considerations suggest that rotational crossing would lead to somewhat better dairy performance, mainly because of more heterozygosity. Predictions based on the performance of adjacent genetic groups as obtained from a comprehensive literature review point in the same direction. Rotational crossbreeding depends on a continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 5 publications
5
26
0
2
Order By: Relevance
“…Both lactation and daily milk yield increased significantly with the rise in Bos taurus blood up to 50% (2721.10 ± 87.36 and 9.77b±0.30, respectively) and then there was no significant change as foreign blood rose to 87.5%. Mounting evidence from the Sudan and other tropical countries (SYRSTAD, 1989;MADALENA et al, 1990;SYRSTAD, 1996;MADALENA, 1998;REGE, 1998) indicates that 50% is probably the optimum level of Friesian blood with regard to the amount of milk produced. SYRSTAD (1989) found that there was no significant difference in milk yield between F 1 crosses of B. taurus and B. indicus and 75% backcrosses to B. taurus.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Both lactation and daily milk yield increased significantly with the rise in Bos taurus blood up to 50% (2721.10 ± 87.36 and 9.77b±0.30, respectively) and then there was no significant change as foreign blood rose to 87.5%. Mounting evidence from the Sudan and other tropical countries (SYRSTAD, 1989;MADALENA et al, 1990;SYRSTAD, 1996;MADALENA, 1998;REGE, 1998) indicates that 50% is probably the optimum level of Friesian blood with regard to the amount of milk produced. SYRSTAD (1989) found that there was no significant difference in milk yield between F 1 crosses of B. taurus and B. indicus and 75% backcrosses to B. taurus.…”
Section: 2mentioning
confidence: 99%
“…high temperature, low feed quality and quantity, disease and parasitic loads challenge) can sustain composite genotypes of up to 50% B. taurus blood. Many studies have indicated the superiority of F 1 crosses over higher grades of both production and reproduction traits in low input production systems prevalent in the tropics (SYRSTAD, 1989;MADALENA et al, 1990;SYRSTAD, 1996;MADALENA, 1998;REGE, 1998;. This should entail changes in the present chaotic practice of applying AI with semen from dairy breeds.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Syrstad, 1996;Ayenew et al, 2009) although longevity results of this study are to be considered with care, due to a small coefficient of determination. The higher disease susceptibility of crossbreds is well documented (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…That this is an incorrect assumption (Syrstad, 1996) but does not stop them from upgrading crossbred levels. It is necessary to train farmers on basic aspects of crossbreeding to clarify this misunderstanding.…”
Section: Discussionmentioning
confidence: 99%